2009
DOI: 10.1111/j.1365-3024.2009.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of ovine keratinocytes stimulated with Psoroptes ovis mite antigen – a preliminary study

Abstract: Sheep scab is caused by the noninvasive mite, Psoroptes ovis, which initiates a profound pro-inflammatory skin response leading to lesion development. To investigate these early events between the skin and the parasite, primary ovine epidermal keratinocyte cultures were generated and challenged with mite derived antigens. The kinetics of the mRNA response of these cells were monitored by microarray. The results indicated that the cells responded within 1 h of challenge, with a significant increase in the pro-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…Increased IL8 expression supports our previous findings from ovine keratinocyte cultures stimulated with P. ovis mite wash and whole mite extract [14]. However, the timing of this response differs between the in vitro and in vivo systems as the previous study had shown that IL8 expression levels began to decline by 24 hpi; whereas this time point represented the peak level in vivo [14]. However, it cannot be ruled out that this response continues to be activated beyond 24 hpi.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Increased IL8 expression supports our previous findings from ovine keratinocyte cultures stimulated with P. ovis mite wash and whole mite extract [14]. However, the timing of this response differs between the in vitro and in vivo systems as the previous study had shown that IL8 expression levels began to decline by 24 hpi; whereas this time point represented the peak level in vivo [14]. However, it cannot be ruled out that this response continues to be activated beyond 24 hpi.…”
Section: Resultssupporting
confidence: 91%
“…IL8 is a potent chemo-attractant and angiogenic factor involved in the chemotaxis of neutrophils, basophils and T-cells, and has also been shown to be involved in eosinophil chemotaxis [96]. Increased IL8 expression supports our previous findings from ovine keratinocyte cultures stimulated with P. ovis mite wash and whole mite extract [14]. However, the timing of this response differs between the in vitro and in vivo systems as the previous study had shown that IL8 expression levels began to decline by 24 hpi; whereas this time point represented the peak level in vivo [14].…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The first approach to investigate the early inflammatory response, was to generate ovine primary keratinocyte cultures challenged with mite derived antigens, and the kinetics of the mRNA response of these cells were monitored by microarray. Authors found that six genes were up-regulated, showing a significant increase in the pro-inflammatory cytokine IL-8 [39]. Afterwards, it was characterized the inflammatory response from sheep skin biopsy samples, achieved through microarrays and qRT-PCR, founding an up-regulation of transcripts for pro-inflammatory cytokine genes IL-1β, IL-6 and IL-8.…”
Section: Discussionmentioning
confidence: 99%